A Smart Chair for Sitting Postures Monitoring and Seat Occupancy Detection - Zaharuddin, Mohd Syahmi Hilmi; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2025)
In recent years, occupational roles often require extended periods of sedentary activity, particularly sitting in front of computer screens. Incorrect sitting postures adopted during such activities can lead to various health issues such as muscular imbalances and spinal misalignment. Therefore, a Smart Chair for Sitting Postures Monitoring and Seat Occupancy Detection is proposed in this work to overcome those health issues. The Smart Chair design incorporates four ultrasonic sensors to actively monitor the distance between the user’s back and the seat cushion. When poor posture is detected, the Blynk application sends alert notifications to the user’s mobile phone. Additionally, the seat occupancy detection system, powered by four Force Sensing Resistor (FSR) sensors, proves useful in multi-user environments.   Real-time alerts via the Blynk application enhance the operational efficiency of the Smart Chair. Validation assessments conducted with three volunteers of varying heights and weights confirmed the effectiveness of the ultrasonic sensors in monitoring sitting postures. The sensors operate consistently with the predefined truth table. Additionally, the validation process for seat occupancy detection, using the same volunteers, demonstrates system reliability and responsiveness. Alert notifications are accurately sent to users’ mobile phones upon detecting physical pressure. In a nutshell, the Smart Chair has demonstrated its effectiveness in continuously monitoring sitting postures and detecting seat occupancy which contributes to a health-conscious and intelligent seating solution, enhancing the overall user experience.